Evaluation of the implementation of Value‐Based Healthcare with a weekly digital follow‐up of lung cancer patients in clinical practice. (12th July 2022) - Misplon, Sarah; Marneffe, Wim; Himpe, Ulrike; Hellings, Johan; Demedts, Ingel
Abstract: Objective: The aim of this study was to evaluate the implementation of Value‐Based Healthcare principles for lung cancer patients in a large Belgian hospital. This hospital implemented a digital platform for the collection of patient‐reported outcomes and the standardisation of care pathways. Also, a follow‐up by the multidisciplinary care team was put in place. Methods: Evaluation was done by employing a mixed method approach with data analysis of all included patients ( n = 201), a pilot study ( n = 30) and semi‐structured interviews with the care team ( n = 5). Results: Overall, 95% of all lung cancer patients of two thoracic oncologists agreed to participate in the digital follow‐up during the period January 2018 to September 2020 (201 participating patients). The response rates of those patients were high: 92% of the weekly questionnaires and 90% of the 6‐weekly ICHOM questionnaires were responded. Based on the pilot study, we conclude that questions are clear and the platform is user‐friendly for 90% of patients in the pilot. The interviews revealed that the weekly follow‐up has a positive impact on the patient–provider communication and makes it easier to discuss psychological and palliative care needs. Conclusion: This study shows a successful implementation of Value Based Healthcare with weekly digital follow‐up. Clinical trial registration is as follows: www.clinicaltrials.gov, NCT04712149.